Publishing and Academic Writing: Experiences of Authors Who Have Published in PROFILE - Melba L. Cárdenas (Profile: Issues in Teachers' Professional Development)
The increase in the publication of academic journals is closely related to the growing interest of research communities as well as of institutional policies that demand visibility of the work done by their staff through publications in highly-ranked journals. The purpose of this paper is to portray the experiences of some authors who published their articles in the PROFILE journal, which is edited in Colombia, South America. Data were gathered using a survey carried out through the use of a questionnaire. The results indicate the reasons the authors submitted their manuscripts, their experiences along the process of publication, and what the publication of their articles in the journal has meant to them. The authors’ responses and the reflections derived from them also show that despite the difficulties faced, there were achievements and lessons learned as well as challenges ahead to ensure the sustainability of the journal and teachers’ empowerment.